2015
DOI: 10.1002/path.4566
|View full text |Cite
|
Sign up to set email alerts
|

The repertoire of somatic genetic alterations of acinic cell carcinomas of the breast: an exploratory, hypothesis‐generating study

Abstract: Acinic cell carcinoma (ACC) of the breast is a rare form of triple-negative (that is, estrogen receptor-negative, progesterone receptor-negative, HER2-negative) salivary gland-type tumor displaying serous acinar differentiation. Despite its triple-negative phenotype, breast ACCs are reported to have an indolent clinical behavior. Here, we sought to define whether ACCs have a mutational repertoire distinct from that of other triple-negative breast cancers (TNBCs). DNA was extracted from microdissected formalin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 67 publications
3
93
0
Order By: Relevance
“…In contrast, Piscuoglio et al [27] did not detect any mutations in TP53 in 20 salivary AcCCs, leading those authors to conclude that from a molecular pathology standpoint, breast AcCCs have far more in common with TNBC than salivary AcCCs. In keeping with these results, Guerini-Rocco et al [31] recently performed massively parallel sequencing analysis of the same cohort of breast AcCCs as Piscuoglio et al [27] and demonstrated a pattern of complex copy number aberrations that also mirrors that seen in TNBC. MLL3 , another likely oncogenic driver in our case, was also mutated in 7% of cases in the breast carcinoma/The Cancer Genome Atlas study [30], making it one of the top five most frequently mutated genes.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, Piscuoglio et al [27] did not detect any mutations in TP53 in 20 salivary AcCCs, leading those authors to conclude that from a molecular pathology standpoint, breast AcCCs have far more in common with TNBC than salivary AcCCs. In keeping with these results, Guerini-Rocco et al [31] recently performed massively parallel sequencing analysis of the same cohort of breast AcCCs as Piscuoglio et al [27] and demonstrated a pattern of complex copy number aberrations that also mirrors that seen in TNBC. MLL3 , another likely oncogenic driver in our case, was also mutated in 7% of cases in the breast carcinoma/The Cancer Genome Atlas study [30], making it one of the top five most frequently mutated genes.…”
Section: Discussionmentioning
confidence: 78%
“…Immunohistochemical profile of the included cases (n=59) was assessed on 4μm-thick sections, using antibodies against ER, progesterone receptor (PR), HER2 and Ki-67 as previously described (23). Positive and negative controls were included in each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Custom oligonucleotides (NimblegenSeqCap) were designed for hybridization capture of the 241 genes (Supplementary Table S3) (28). Barcoded sequencing libraries were prepared (New England Biolabs) using 50ng to 250ng DNA and pooled at equimolar concentrations into a single capture reaction as previously described (23, 28). Paired-end 76bp reads were generated on the Illumina HiSeq2000.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the normal tissue was microdissected to be devoid of any neoplastic cells as previously described. 29,30 Genomic DNA from each tumor component and matched normal tissue was extracted using the DNeasy Blood & Tissue Kit (Qiagen), according to the manufacturer’s instructions, and quantified using the Qubit 2.0 Fluorometer (Invitrogen, Life Technologies).…”
Section: Methodsmentioning
confidence: 99%